1995
DOI: 10.1021/bi00005a017
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of lantibiotic-induced permeabilization of phospholipid vesicles

Abstract: Nisin is a cationic polycyclic bacteriocin secreted by some lactic acid bacteria. Nisin has previously been shown to permeabilize liposomes. The interaction of nisin was analyzed with liposomes prepared of the zwitterionic phosphatidylcholine (PC) and the anionic phosphatidylglycerol (PG). Nisin induces the release of 6-carboxyfluorescein and other small anionic fluorescent dyes from PC liposomes in a delta psi-stimulated manner, and not that of neutral and cationic fluorescent dyes. This activity is blocked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
207
2
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(223 citation statements)
references
References 30 publications
8
207
2
3
Order By: Relevance
“…Earlier evidence has shown that this is also true for ring k; acid hydrolysis at Dha 5 in nisin ~ a2 amide leads to loss of tctivity [13], but the Dha5Ala mutant retains full antibacterial tctivity [12], showing that it is the intact ring A, rather than he dehydro residue at position 5, which is required for this tctivity. The 'wedge' model for the formation by nisin of transient pores in the bacterial membrane by induction of non-bilayer structures [10,26] postulates that the N-terminal part of nisin, comprising rings A-C, is responsible for binding of nisin to the membrane surface and/or its oligomerisation, while the more cationic C-terminal part of the molecule plays a role in pore formation. The present evidence is consistent with the idea that intact rings A and C are required for this binding function, and suggests that some pore formation is possible in the absence of the cationic C-terminal segment.…”
Section: Growth-inhibitory Activity Of Fragments Of Nisinmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier evidence has shown that this is also true for ring k; acid hydrolysis at Dha 5 in nisin ~ a2 amide leads to loss of tctivity [13], but the Dha5Ala mutant retains full antibacterial tctivity [12], showing that it is the intact ring A, rather than he dehydro residue at position 5, which is required for this tctivity. The 'wedge' model for the formation by nisin of transient pores in the bacterial membrane by induction of non-bilayer structures [10,26] postulates that the N-terminal part of nisin, comprising rings A-C, is responsible for binding of nisin to the membrane surface and/or its oligomerisation, while the more cationic C-terminal part of the molecule plays a role in pore formation. The present evidence is consistent with the idea that intact rings A and C are required for this binding function, and suggests that some pore formation is possible in the absence of the cationic C-terminal segment.…”
Section: Growth-inhibitory Activity Of Fragments Of Nisinmentioning
confidence: 99%
“…The simplest explanation of the effects of nisin 1-12 is that it competes with nisin for some site which is essential for pore formation. The observation that nisin is able to form pores in protein-free liposomes [26] makes it unlikely that this essential site is a protein, but two other possibilities remain. First, nisin 1-12 could compete for a site on the cell membrane to which nisin must bind as a preliminary to pore formation -probably phosphatidyl glycerol [10,26].…”
Section: Competitive Antagonism Of the Antibacterial Action Of Nisinmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact molecular mechanism of the growth-inhibiting effect of nisin is still not fully understood, although several studies have found indications that nisin interacts with the bacterial cell membrane forming pores ultimately leading to cell lysis (Hurst, 1981 ;Gao et al, 1991 ;Driessen et a]., 1995;Sahl et al, 1995).…”
mentioning
confidence: 99%
“…For intact cells the threshold potential is between -50 mV and -80 mV at pH 7.5 and below -50 mV at pH 5.5 (Sahl et al, 1987). In vitro studies have indicated that the activity of nisin is highly dependent on the phospholipid composition (Gao et al, 1991 ;Garcia Garceri et al, 1993;Driessen et al, 1995).…”
mentioning
confidence: 99%